Development of Spiritual and Social Attitude Mutabaah Books in Islamic Religious Education Subjects Grade VIII Junior High School - Ikhsanawati, Hanifah (Journal of Indonesian Progressive Education, 2024)
The existence of the affective realm is a challenge in the implementation of the character-based 2013 Curriculum, which in practice is not optimal due to the assessment instruments that are not yet standard and the limitations of teachers in conducting comprehensive affective assessments. This research aims to develop mutabaah books as a tool for teachers to complete the assessment of students' spiritual and social attitudes in Islamic Religious Education (PAI) grade VIII at SMP N 1 Bantul. The method used is Research and Development (RnD) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model from Dick and Carey, involving interviews, observations, and questionnaires as data collection techniques, as well as qualitative-to-quantitative analysis. The product of this study was validated with a result of 87.5% in the "valid" category and an effectiveness of 85.5%, classified as "very effective". This mutabaah book is expected to increase the achievement of the affective realm in a structured manner in the implementation of the 2013 Curriculum.